The Role of Business Education in the Implementation of Financial Check List in Financial Management Courses - Saut Maruli Tua Pandiangan; Lindari Wau; Ariawan Ariawan; Fithriah Napu; Uli Wildan Nuryanto (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this research is to analyze the role of business education in the implementation of financial check list in financial management courses. This type of research is quantitative research. Population in this study are 16 students consisting of majoring in 7 Business Administration, 4 Accounting, and 5 Financial Management in Semester 3, academic year 2022 to 2023, on Politeknik Unggulan Cipta Mandiri who are taking financial management courses. Sampling is carried out by means of saturated sample. Because it uses a saturated sample, there are 16 students who are taken financial management courses. Data analysis technique through inferential using paired t-test. This different test model is used to analyze the research model before and after students complete the application of financial check list. The results of the study show that there are differences before and after students complete the implementation of financial check list in financial management in the framework of the role of business education